Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1126/sciadv.aat4229
|View full text |Cite
|
Sign up to set email alerts
|

Voltage control of unidirectional anisotropy in ferromagnet-multiferroic system

Abstract: Magnetoelectricity enables a new class of nonvolatile, ultralow-energy computing with quantum materials for AI & Moore’s law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 35 publications
4
51
0
1
Order By: Relevance
“…It is found that the coupling between antiferromagnetic domain patterns and ferroelectric domains only occurs with the 71° and 109° polarization switching, while it cannot be found with the 180° ferroelectric polarization switching. This work is a crucial first step in the exploration of approaches for researchers into investigations of the ME coupling property of BFO [35,104,[106][107][108].…”
Section: Magnetoelectric Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the coupling between antiferromagnetic domain patterns and ferroelectric domains only occurs with the 71° and 109° polarization switching, while it cannot be found with the 180° ferroelectric polarization switching. This work is a crucial first step in the exploration of approaches for researchers into investigations of the ME coupling property of BFO [35,104,[106][107][108].…”
Section: Magnetoelectric Couplingmentioning
confidence: 99%
“…A electrically switchable exchange bias is observed at the interface between the BFO and giant magnetoresistance. Adapted with permission from Ref [108]…”
mentioning
confidence: 99%
“…BFO is a rare room-temperature multiferroic with the largest spontaneous polarization among single-phase compounds known to date, and may be soon used in nano-devices 20 . Three types of ferroelectric DWs in the rhombohedral phase are distinguished by the number of polarization components being reversed 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetoelectric multiferroics have emerged as an attractive material system due to their multifunctionality for a variety of potential device applications in energy and memory technologies [ 1 , 2 , 3 ]. These devices are mainly based on epitaxial thin-film heterostructures with smooth surfaces and interfaces at atomic scale [ 2 , 4 , 5 , 6 , 7 ]. Recent advances in epitaxial growth techniques have enabled the synthesis and design of multiferroic heterostructures that give rise to a variety of multifunctional properties [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%